Market-led Extension in Mid-hills of North West Himalayas: Experiences and Impact - S.R.K. Singh, K. Srinivas , Mukesh Kumar , N.K. Hedau, U.S.Gautam (Indian Journal of Extension Education, 2022)
In the rural area of North West Himalayas, off-season vegetables are grown predominately as a means of livelihood. However, the farmers are unable to harness the potential benefits of vegetable cultivation due to lack of improved production technologies, poor access of market information and inadequate extension support. To overcome this, market-led extension (MLE) approach was implemented in Tarikhet block of Almora district. Using MLE approach, farmers were trained in selection of quality inputs, market situation, price trend analysis, and scientific vegetable cultivation. There was considerable increase in awareness (83.62%), knowledge (65.25%) and adoption (74.74%) of the farmer in adopted villages. The analyzed data revealed that the approach has resulted in increased yields of tomato (115.8 to 170.2 q/ha), capsicum (72.1 to 118.6 q/ha), French bean (52.2 to 83.1 q/ha) and pea (68.7 to 86.7 q/ha) beside better quality of produce. As a result, the gross income of farmers increased by 27.0 – 66.0 percent, over existing technology and market strategies, practiced before the project implementation. This study suggests the great potential of MLE approach for enhancing income of the hill farmers.